ANALISIS SWOT TERHADAP USAHA TOKO IMELDA PONSEL TELUKDALAM NIAS SELATAN - Paskalis Dakhi; Progresif Buulolo; Trinitaktis Harita (Balance: Jurnal Riset Akuntansi dan Bisnis, 2022)
Imelda Ponsel Telukdalam South Of Nias is a store in Nias is a trade in electronic goods and specifically mobile phones in various brand. The study is intended to answer how and whether the Imelda ponsel store platform has a swot strategy for its business. The method of data analysis technique with a descriptive qualitative approach. Based on the analysis of the swot strategy to its business, which can be proven from the analysis of the internal and external factors IFAS and EFAS, and thus the coordinate point of 1.724 : 1.01 on the swot diagram explains that the mobile imposition store is in the province supporting the growth/growth strategy and the enterprise is still in prime condition. These conditions provide an opportunity for maximum profits because companies have the opportunity and the power to do both the development and expansion of businesses.